Intramembrane proteolysis by rhomboids: catalytic mechanisms and regulatory principles. - Vinothkumar, K; Freeman, M (2013)
Rhomboids are intramembrane serine proteases that cleave membrane proteins within the bilayer, and which control a wide variety of biological processes. Recent structures of Escherichia coli rhomboids in complex with mechanism-based inhibitors provide insight into their catalytic mechanism. The inhibitor structures also reveal potential substrate-binding sites within the enzyme and provide a template for modeling substrate binding at the active site. The regulation of rhomboid activity exploits the different membrane compartments in cells to segregate enzyme and substrate. Catalytically inactive rhomboid-like proteins called iRhoms provide another form of regulation, by interacting with rhomboid substrates and preventing their cleavage. Extramembranous domains of rhomboids may play an as yet unexplored role in substrate recognition and regulation.